Determinan Rasio Keuangan Terhadap Harga Saham Pada Perusahaan Manufaktur Sektor Multi Industri Yang Terdaftar di Indeks Saham Syariah Indonesia Tahun 2016-2020 - Ambok Pangiuk (ILTIZAM Journal of Shariah Economics Research, 2022)
The purpose of this study was to determine the effect of financial ratio variables in the form of: Return on Assets (ROA), Earning Per Share (EPS), Debt to Equity Ratio (DER), Current Ratio (CR), and Total Asset Turn Over (TATO), on stock prices in Manufacturing Companies in the Multi-Industrial Sector listed in the Indonesian Sharia Stock Index (ISSI) Period (2016-2020). The sample used in this study were 22 companies taken from the purposive sampling method. This study uses a quantitative approach with secondary data collection methods on company reports. The analytical method used in this study is Panel Data Regression Analysis using Statistical Analysis tools in the form of Eviews. The results of this study indicate that the Partial Return on Assets (ROA), Current ratio (CR), Total Asset Turn Over (TATO) have a negative and insignificant effect on stock prices significant to stock prices. And the variables Debt to Equity Ratio (DER) and Earning Per share (EPS) have a positive and significant effect on stock prices. This study also shows that simultaneously (Test F) Return on assets (ROA), Earnings Per share (EPS),Debt to equity Ratio (DER), Current Ratio (CR), and Total Asset Turn Over (TATO) have an influence on the price Shares in Manufacturing Companies in the Multi-Industrial sector listed in the Indonesian Sharia Stock Index (ISSI) for 2016-2020.